The prognostic significance of pretreatment serum γ-glutamyltranspeptidase in primary liver cancer: a meta-analysis and systematic review. Issue 6 (28th November 2018) - Ou, Yang; Huang, Junwei; Yang, Liping
Abstract : Aim: To assess the prognostic value of the pretreatment serum γ-glutamyltranspeptidase (GGT) level in patients with primary liver cancer (PLC).Methods: Relevant studies were systematically searched online on Web of Science, PubMed, and Embase databases published until 9 October 2018. The end points were overall survival (OS), recurrence-free survival (RFS), and disease-free survival (DFS). Meta-analysis was conducted using hazard ratio (HR), and its 95% confidence interval (CI) as effect measure.Results: A total of 33 eligible studies with 9238 patients with PLC were included in this meta-analysis. The synthesized analysis showed that that higher serum GGT level was significantly related to poorer OS (HR: 1.79, 95% CI: 1.66–1.93, P <0.01), RFS (HR: 1.60, 95% CI: 1.46–1.77, P <0.01), and DFS (HR: 1.52, 95% CI: 1.33–1.73, P <0.01) of patients with PLC. Subgroup analyses demonstrated that the negative prognostic impact of higher serum GGT level on OS and RFS was still of significance regardless of ethnicity, pathological type, sample size, cut-off value, first-line treatment, and analysis type.Conclusion: The pretreatment serum GGT might be a predictive factor of poor prognosis for PLC patients.